Active load control of wind turbine blade section with trailing edge flap: Wind tunnel testing. (December 2014) - Lee, Jong-Won; Han, Jae-Hung; Shin, Hyung-Ki; Bang, Hyung-Joon
In order to reduce the cost of energy, the rotor diameter of wind turbine has been continuously increased. Fatigue load becomes more important as wind turbines increase in size. The reduction of fatigue load can result in increased component lifetimes, reduced maintenance requirements, and an overall lower cost of energy. In this article, a load reduction analysis and experiment are performed to show the load reduction abilities of an active aerodynamic load control device, namely trailing edge flaps, in the operation of large wind turbines. Through numerical simulations that use trailing edge flaps as active aerodynamic load control devices on wind turbines, a 30%–50% reduction in the standard deviation oscillations of root bending moment from the mean value was achieved. To validate the active load control analysis and show the potential of the trailing edge flap for load reduction, an active load control experiment of the wind turbine blade was performed. The experimental model was developed using a non-rotating blade equipped with a trailing edge flap and load-cell sensors to facilitate feedback control. A controller is based on the proportional–derivative control in order to minimize the blade root load variation in the flapwise direction. Through the experiment, a 20%–30% reduction in the standard deviation oscillations of blade root load from the mean value was achieved.